Perioperative Tight Glycemic Control: The Challenge of Bariatric Surgery Patients and the Fear of Hypoglycemic Events - Joseph, Bellal (The Permanente Journal, 2007)
Background: Tight glycemic control (TGC) is rapidly becoming a standard of care for all hospitalized patients. However, fear of hypoglycemia has proven a potent barrier to adoption of such initiatives by physicians and medical staff. Henry Ford Hospital has pursued aggressive glycemic control for all hospital patients. Because the initial standard TGC protocol (TGCP) was insufficient to improve glycemic control in our bariatric surgery patients, we hypothesized that a more intensive protocol would be necessary to improve glycemic control for this group. Methods: As part of an institutional quality control project involving TGC, we reviewed medical records for the bariatric surgery patients at our hospital. We divided the populations into three subgroups: prior to TGC (A), initial hospital rollout TGC (B), and intensive bariatric TGC protocol (C). Patient populations were compared using hospital administrative databases and clinical chart review. Metrics for successful glycemic control included percent hypoglycemia (glucose <50 mg/dL), in-range percent (glucose 80–150 mg/dL), mild hyperglycemia (glucose 151–250 mg/dL), and major hyperglycemia (glucose >250 mg/dL). Results: The percent in range for group C improved to 71% but was not statistically different from the values for groups A and B. The incidence of hyperglycemia was significantly decreased in group C as compared with groups A and B at both the minor (20% vs 31% and 27%) and major levels (1% vs 4% and 2%) (p < 0.001).There were no differences in the rates of hypoglycemia. Conclusion: As an ongoing quality improvement process, our institution has pursued TGC for all of its patients. Glucose control in bariatric surgery patients is resistant to standard TGCPs. An initial intensive TGCP can be safely implemented in bariatric surgery patients with no increase in the number of hypoglycemic events. This work represents follow-up of several plan, do, check, act (PDCA) cycles related to improvement with a hospital-wide TGCP.